Hypericum perforatum: Traditional uses, clinical trials, and drug interactions - Seyedeh Zahra Nobakht; Maryam Akaberi; Amirhooshang Mohammadpour; Ali Tafazoli Moghadam; Ahmad Emami (Iranian Journal of Basic Medical Sciences, 2022)
Hypericum perforatum (Hypericaceae), known as Saint John’s wort (SJW), has been used in different systems of traditional medicine such as Chinese traditional medicine, Greek traditional medicine, and Islamic traditional medicine. The plant and its active constituents such as hyperforin and hypericin have a wide range of medicinal uses, particularly as anti-depressant, wound-healing, and antibacterial agents. In recent decades, many clinical trials have been performed to investigate the safety and efficacy of this medicinal plant. However, to the best on our knowledge, there is no comprehensive review article in this regard. In the current study, we aim to have a comprehensive review of the clinical trials of SJW to evaluate its efficacy and safety as well as its application in traditional medicine. Clinical studies investigating the safety, interactions, and efficacy of SJW were identified and summarized, including contributions from 2000 until December 2021. According to the results, these clinical studies were divided into three main categories based on the type of disease: psychiatric, endocrine, and skin problems. Important details of the studies, including the type and duration of the study, the type and percentage of the effective compounds or the extract used, the number of patients, and the obtained results were also discussed. In addition, co-administration and drug interaction of SJW with other drugs were summarized. SJW is a valuable medicinal plant, especially for psychiatric disorders. However, precautions should be taken while administrating the plant.